A Minimum Wage May Increase Exports and Firm Size Even with a Competitive Labor Market - Eliav Danziger; Leif Danziger (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper explores how a minimum wage affects a firm's behavior with a competitive labor market and an uncertain export cost. The model provides several novel insights which are consistent with recent empirical evidence. Thus, a minimum wage increases an exporter's foreign-market size and may cause a non-exporter to start exporting. The foreign-market size may increase so much that, although the home-market size decreases, the overall firm size increases.
Keywords: J30; 330; minimum wage; exports; firm size